Automated prior knowledge-based quantification of neuronal patterns in the spinal cord of zebrafish - Stegmaier, Johannes; Shahid, Maryam; Takamiya, Masanari; Yang, Lixin; Rastegar, Sepand; Reischl, Markus; Strähle, Uwe; Mikut, Ralf (Bioinformatics, 2014)
Abstract. Motivation: To reliably assess the effects of unknown chemicals on the development of fluorescently labeled sensory-, moto- and interneuron populatio
Published: 17 October 2013
Gesehen am 16.09.2020